Legal Reconstruction of the Distribution of Common Property through a Study of Sociological Jurisprudence - Mamonto, Andi Annisa Nurlia; Putri, Viorizza Suciani; Salsabila, Nazwa Milka (Dinasti Research, 2025)
This study examines the division of joint property post-divorce using the sociological jurisprudence framework established by Roscoe Pound, emphasizing critiques of the normative stipulations in Article 97 of the Compilation of Islamic Law, which mandates an arithmetic division into semi-halves. The primary issue analyzed is the degree to which sociological methodologies may discern positive legal deficiencies in achieving substantive justice when the contributions of husband and wife are socially and economically inequitable. The used technique is normative juridical, using a theoretical approach that involves the examination of statutes, regulations, legal theory, and judicial practice. The study's findings indicate that inflexible positive legislation may overlook domestic and non-financial contributions, particularly from the wife. In some verdicts, judges use contra legem as a manifestation of judicial daring to maintain substantive justice grounded in genuine contributions. The sociological jurisprudence method facilitates a contextual and adaptive reconstruction of family law in response to societal processes. The allocation of communal assets should be grounded not only in the idea of formal equality but also in the acknowledgment of genuine contributions that often remain obscured by domestic labor and power dynamics inside the home